APPROACHES TO ANTIRECESSION ENTERPRISE MANAGEMENT CONCEPTUALIZATION - Olga V. Fateyeva (Advanced Engineering Research)
Some approaches to the antirecession enterprise management conceptualization are offered: the concep t, the d etection of the crisis signs, the definition of the crisis stages, the choice of the strategies and m echanisms of their realization.